P161 INCIDENTAL FINDING OF QUADRICUSPID AORTIC VALVE IN A YOUNG ASYMPTOMATIC PATIENT. (18th May 2022) - Ceriello, L; Salvatore, T; De Rosa, M; Marrone, G; Ruggieri, B; Fabiani, D; Napoletano, C
Abstract: Background: Quadricuspid aortic valve (QAV) is a rare congenital heart disease, eventually leading to aortic regurgitation (AR) and heart failure. In up to one–third of patients, QAV is associated with other coexisting cardiac defects, particularly aortic dilation and coronary arteries abnormalities. Case Report: A 48–years old man without significant past medical history was referred to the Cardiologist for newly diagnosed arterial hypertension. The patient was asymptomatic and no abnormal findings were noticed on physical examination. Transthoracic echocardiography showed normal end–diastolic volume and diameter of the left ventricle and preserved systolic function. However, a mild dilation of the aortic root (40 mm) and ascending aorta (38 mm) with concomitant moderate–to–severe AR were described. Transoesophageal echocardiogram (TOE) was performed to better visualize the aortic valve anatomy and to define the exact mechanism of the AR. 2D–TOE revealed a QAV with equal–sized cusps (type A according to the Hurwitz–Roberts classification), with a central quadrangular coaptation defect and a moderate AR (vena contracta width: 4 mm) [Fig. 1–2 ]. The regurgitant jet conditioned a pseudo–prolapse of anterior mitral leaflet with consequent mild–to–moderate mitral regurgitation. 3D–TOE allowed a better characterization of valve morphology and the individuation of the sole left coronary artery ostium. A coronary artery computed tomography was requested to investigate a probable abnormal origin of the right coronary artery. The patients was subsequently addressed to a regular clinic and echocardiographic follow–up for the surveillance of AR and aortic dimensions and a prompt management of an eventual symptoms onset. Discussion: We describe a rare case of type A QAV with moderate AR, mild dilation of aortic root and ascending aorta and suspected anomalous origin of the right coronary ostium. The broad diffusion of imaging techniques has recently led to an increase of incidental diagnosis, even in asymptomatic patients. The complex valve anatomy, with many possible morphologies of the supernumerary cusp, and the association with other congenital defects, particularly anomalous coronary ostia location, pose many technical issues in case of valve replacement. A multimodality imaging approach is essential for a clear description of valve morphology and coronary anatomy to avoid intraoperative complications in both surgical and percutaneous valve replacement procedures.